Spectrum and Frequencies of Genes for Inherited Hearing Loss in Southwestern Chinese Families - Xiao, Yuanyuan; Wang, Li; Zhou, Cong; Xie, Hanbing; Huang, Shuang; Wang, Jing; Liu, Shanling (Genetic testing and molecular biomarkers, 2025)
Inherited hearing loss is an extremely heterogeneous and often ethnicity-specific disorder, with more than 150 genes identified to date. Thus, clinical diagnosis is challenging, particularly because of the thousands of different severe causal mutations between populations. In this study, we aimed to identify the mutational spectra associated with hearing loss in 89 Southwestern Chinese families. We used a hearing loss-targeted panel to sequence 163 genes known to cause or be candidate genes for hearing loss. The targeted panel was implemented to 89 families with syndromic or nonsyndromic hearing loss. Of the total 89 patients, 55 patients carried 101 pathogenic/likely pathogenic alleles, providing a genetic diagnosis in 61.80%. variants were predominant, with a frequency of 43.6% among all variants, followed by variants of (31.7%), (5.9%), and (5%). These 4 genes accounted for 80.56% (87/108) of all identified alleles. Furthermore, 3 of the 89 patients carried 7 alleles of unknown significance. In total, 45 variants were identified, including 35 variants reported in the Human Gene Mutation Database Professional and 10 novel variants that had not been previously reported. Our findings provide a survey of the mutation spectrum in patients with hearing loss from Southwestern Chinese families. This highlights the fact that genomic sequencing with a selected gene panel specific to hearing loss is effective for its genetic diagnosis.